Efficacy and safety of thrombectomy with or without intravenous thrombolysis in the treatment of acute basilar artery occlusion ischemic stroke: an updated systematic review and meta-analysis - Tian, Shuyi; Zou, Mengqing; Li, Dan; Zhou, Hang; Wang, Chenghan; Liu, Qianshuo; Gao, Lianbo (Frontiers in Neurology, 2024)
Background Mechanical thrombectomy (MT) is a well-established treatment for acute basilar artery occlusion (BAO)-induced posterior circulation ischemic stroke. Objective The objective of the study was to compare the outcomes of endovascular therapy (EVT) with and without bridging intravenous thrombolysis (IVT) in patients with acute BAO, using an updated meta-analysis. Methods A systematic literature search was conducted to identify studies that compared the efficacy and safety of EVT with and without IVT in the treatment of acute BAO ischemic stroke. The extracted data included sample size, patient age, National Institutes of Health Stroke Scale (NIHSS) scores, 90-day modified Rankin Scale (mRS) scores of 0–2 and 0–3, mortality rates, symptomatic intracranial hemorrhage (sICH), and occurrence of subarachnoid hemorrhage (SAH). Results Five studies that included a total of 1,578 patients (594 IVT + EVT vs. 984 EVT), met the inclusion criteria and were analyzed. The meta-analysis demonstrated that bridging IVT was associated with a higher likelihood of achieving a 90-day mRS score of 0–2 (41% vs. 34%; OR = 1.35, 95% CI 1.09–1.68, p = 0.006). Furthermore, the mortality rate was significantly lower in the IVT + EVT group than in the direct EVT group (25% vs. 30%; OR = 0.70, 95% CI 0.55–0.89, p = 0.003), with low heterogeneity observed (I2 = 0.0%, p = 0.78). However, there were no significant differences between the groups regarding the rates of sICH (5% vs. 6%; OR = 0.85, 95% CI: 0.52–1.39, p = 0.53), SAH (3% vs. 3%; OR = 0.93, 95% CI: 0.39–2.22, p = 0.87), perforation (2% vs. 3%; OR = 0.71, 95% CI 0.26–1.95, p = 0.51), and dissection (3% vs. 2%; OR = 0.97, 95% CI: 0.13–7.14, p = 0.98). Conclusion Bridging IVT in conjunction with EVT was associated with better functional outcomes and reduced mortality rates in patients with acute ischemic stroke (AIS) due to BAO compared to EVT alone, without an increased risk of sICH, SAH, perforation, and dissection. In addition, the benefit of bridging IVT to EVT appeared to be more pronounced in European patients than in Asian patients compared to EVT alone. However, the conclusions of this study are not definitive and require validation through large-scale randomized controlled trials (RCTs) to draw more robust conclusions. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024531363.